Filosofi Tari Sekapur Sirih Pada Masyarakat Jambi - Khoironi, Khoironi (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
Please This research explores the philosophy of Sekapur Sirih Dance in the context of the Jambi community. The dance is not just a series of movements but a cultural heritage reflecting local wisdom and values deeply rooted in the daily lives of the Jambi people. The results show that Sekapur Sirih Dance is not merely entertainment but also a symbol of harmony and togetherness in the lives of the Jambi community. Each movement, from body posture to facial expressions, is filled with profound meanings that depict values such as unity, diversity, and the balance between humans and nature. The research also discusses the influence of religion and local beliefs in the philosophy of Sekapur Sirih Dance. The gentle and rhythmic movements create a sacred atmosphere, connecting the community with their spiritual heritage. The philosophy of Sekapur Sirih Dance embodies local wisdom, which is continually preserved and highly regarded by the Jambi people as an integral part of their cultural identity. This study contributes to a deeper understanding of cultural values through traditional performing arts, with a specific focus on the context of the Jambi community.